Qanat and Its Challenges in Ferdows County-Iran - Bazzi, Khodarahm (International Journal of Geography and Geology, 2012)
The purpose of digging qanat or subterranean canal, this domestic and national art of Iranian is an operation of underground water that today we use it less than the past. Reviving of this traditional method of irrigating is just possible by increasing its yield from an economical perspective. In the recent decade because of the cost of labor, force and changes in ownership basis and negligence of public sector put the most of qanat toward aridness and reduced its importance. In this paper, we will study the effects of bemire Baladeh’sqanat. Baladeh’sqanat that supplied water for agriculture in Ferdows city, nowadays this qanat almost is dried. In the past people made the water of this qanat bemire for prevention of osmosis to the ground, nowadays the yield of water has been decreased and because of inattention in its maintenance and reparation, it became dry. Among the product that was irrigated in the past by water of qanat was saffron and decreased the importance of qanat’s water.